2017
DOI: 10.1039/c7cp02173a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrate promoters on gas uptake

Abstract: Gas hydrate technology is considered as a promising technology in the fields of gas storage and transportation, gas separation and purification, seawater desalination, and phase-change thermal energy storage. However, to date, the technology is still not commercially used mainly due to the low gas hydrate formation rate and the low gas uptake. In this study, the effect of hydrate promoters on gas uptake was systematically studied and analyzed based on hydrate-based CH storage and CO capture from CO/H gas mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Experiments 5-8 had initial methane hydrate saturations varying from 28% to 35% caused by differences in gas uptake due to the presence of different chemicals [87] and pure CO 2 injection pressure varied from 50 to 60 bar. Due to initial water saturation above 40%, it was assumed that the hydrate morphology was pore-filling [84,88].…”
Section: Ch 4 Recovery and Co 2 Storage At Same Initial Water Saturation In The Presence Of Different Hydrate Formers And Watermentioning
confidence: 99%
“…Experiments 5-8 had initial methane hydrate saturations varying from 28% to 35% caused by differences in gas uptake due to the presence of different chemicals [87] and pure CO 2 injection pressure varied from 50 to 60 bar. Due to initial water saturation above 40%, it was assumed that the hydrate morphology was pore-filling [84,88].…”
Section: Ch 4 Recovery and Co 2 Storage At Same Initial Water Saturation In The Presence Of Different Hydrate Formers And Watermentioning
confidence: 99%
“…Thermodynamic promoters, for example, tetrahydrofuran (THF), are capable of forming gas hydrates themselves at moderate conditions in terms of pressure and temperature, allowing other guests to fill the remaining empty cavities, whereby these other molecules are entrapped in the gas hydrate phase as well [34]. Furthermore, the polarity of the thermodynamic promoter affects gas diffusion via the gas-liquid interphase, which influences the selectivity and gas uptake of a gas hydrate separation process [35]. The mode of operation of kinetic promoters, essentially surfactants, is based on accelerating gas hydrate formation by reducing the surface tension, which leads to improved mass transport of gas into the liquid phase [36].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 hydrate was once thought as one of the potential intermediates for carbon capture and separation . It has been reported that CO 2 hydrate is of structure I (s‐I) including 46 H 2 O molecules and up to 8 CO 2 molecules with both small (5 12 ) and large (5 12 6 2 ) cages in a ratio of 1:3 . It should be noted that CO 2 molecules are reported to approximately occupy most large cages and few small cages .…”
Section: Introductionmentioning
confidence: 99%